2019
DOI: 10.2134/agronj2019.01.0037
|View full text |Cite
|
Sign up to set email alerts
|

Basis of Atrazine and Mesotrione Synergism for Controlling Atrazine‐ and HPPD Inhibitor‐Resistant Palmer Amaranth

Abstract: Palmer amaranth (Amaranthus palmeri S. Watson) resistant to atrazine [6‐chloro‐N‐ethyl‐N’‐(1‐methylethyl)‐1,3,5‐triazine2,4‐diamine] and 4‐hydroxyphenylpyruvate dioxygenase (HPPD)‐inhibiting herbicides was confirmed in a seed corn (Zea mays L.) production field in Nebraska, in 2014. Neither atrazine nor HPPD inhibitors (mesotrione [2‐(4‐mesyl2‐nitrobenzoyl)‐3‐hydroxycylohex‐2‐enone], tembotrione {2‐[2‐chloro‐4‐(methylsulfonyl)‐3‐[(2,2,2‐trifluoroethoxy) methyl]benzoyl]‐1,3‐cyclohexanedione}, or topramezone {[3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…However, some plants were not effectively controlled by this tank mixture. Such improvement in control can be attributed to the synergism often observed with tank mixing PS II- and HPPD-inhibitor herbicides ( Abendroth et al, 2006 ; Chahal et al, 2019a ). Additionally, the commercial pre-mixture of bromoxynil (PS II-inhibitor) and pyrasulfotole (HPPD-inhibitor) performed poorly in comparison to a tank mix of atrazine and mesotrione.…”
Section: Discussionmentioning
confidence: 99%
“…However, some plants were not effectively controlled by this tank mixture. Such improvement in control can be attributed to the synergism often observed with tank mixing PS II- and HPPD-inhibitor herbicides ( Abendroth et al, 2006 ; Chahal et al, 2019a ). Additionally, the commercial pre-mixture of bromoxynil (PS II-inhibitor) and pyrasulfotole (HPPD-inhibitor) performed poorly in comparison to a tank mix of atrazine and mesotrione.…”
Section: Discussionmentioning
confidence: 99%
“…To find which herbicides were synergistic we created a matrix of 24 herbicides, where 20 herbicides represented one mode of action each, and four herbicides had an unknown mode of action ( Table 2). The herbicides chosen for screening are widely used and included three molecules (clomazone, mesotrione and atrazine) for which well-documented cases of synergy are known as positive controls (Keifer et al, 1990, Abendroth et al, 2006, Bollman et al, 2006, Armel et al, 2007, Woodyard et al, 2009b, Walsh et al, 2012, Kohrt and Sprague, 2017, Chahal et al, 2019 To detect synergistic herbicide combinations, the 276 possible pairwise mixtures of 24 herbicides were made and screened using Arabidopsis thaliana grown on agar plates. For each possible combinations (276), a single sub-lethal concentration for each herbicide was used.…”
Section: Resultsmentioning
confidence: 99%
“…Three herbicides stood out in these synergies; three of the pairs included mesotrione, two included clomazone and two included atrazine. Two combinations (mesotrione-atrazine and clomazone-atrazine) (Keifer et al, 1990, Abendroth et al, 2006, Bollman et al, 2006, Armel et al, 2007, Woodyard et al, 2009b, Walsh et al, 2012, Kohrt and Sprague, 2017, Chahal et al, 2019 were previously reported in the literature, which showed that one-dose screening was sensitive enough to detect these known synergistic mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The post‐emergence application of a three‐way mixture of glyphosate (HRAC group G), mesotrione and S ‐metolachlor in addition to atrazine within 21 days of the pre‐emergence application is advocated for season‐long, overlapping residuality in glyphosate‐tolerant corn. The synergistic effect of atrazine and mesotrione in the four‐way mixture and other related products further protects against resistance evolution in key weeds 73,74 . Similar season‐long residual programs include a mixture of metribuzin (HRAC group C1) and S ‐metolachlor applied pre‐emergence followed by S ‐metolachlor + fomesafen (HRAC group E) 30 days later for controlling glyphosate‐resistant A. palmeri and A. quitensis populations in soybean in Argentina.…”
Section: Development Of Sustainable Weed Management Programsmentioning
confidence: 99%